Analisis Peningkatan Kemampuan Representasi Matematis Siswa SMA Ditinjau dari Perbedaan Gender - Izwita Dewi; Sahat Saragih; Dewi Khairani (Didaktik Matematika, 2017)
Mathematical representation is one of the mathematical higher order thinking skills, as a tool or way of thinking in communicating mathematical ideas. Referring to a research about the inconsistency of a mathematical communication profile involving gender differences and the phenomenon of more female students than men right now, there appears to be an allegation that there is a connection between gender differences and students mathematical representation. The purpose of this study is to analyze the improvement of students' mathematical representation capability in terms of gender differences. Subjects in this research were students of class X of High School in Medan, Indonesia, consisting of 13 men and 19 women. The research instrument is a mathematical representation test consisting of 4 questions. Data analysis to find out how the category of improvement of students mathematical representation, using index of N-gain. The results of the research are: (1) the improvement of mathematical representation ability in the lower and middle categories of male students is higher than female students, (2) there is no male students have high category mathematical representation, but there are female students have high category mathematical representation abilities, and (3) the ability of representation to make mathematical models and explain the verbal language of male students is higher than female students. While the representational ability of making tables and drawing female students is higher than male students. The implication of the research is needs to do deeper research to see the relationship of mathematical representation ability with the students' mathematical ability profile.